Pro dan Kontra Merdeka Belajar - Lukman Hadi (Jurnal Ilmiah Wahana Pendidikan, 2020)
Freedom to learn is the Ministry of Education and Culture's new policy. Freedom to learn is getting the attention of the community, especially teachers. The objective of this study was to describe the level of student approval towards this policy. To achieve the objective, survey research was conducted. A total of 42 students of the Chemistry Education Program who were taking the Chemistry Teaching and Learning Strategies Class were asked to fill out a questionnaire. According to data analysis, the policy generated approval more than disapproval among students